Agreement between the Clinical Pulmonary Infection Score and NHSN criteria for surveillance of Ventilator Associated Pneumonia - Safdar, Nasia; O'Horo, John Charles; Mak, Rosa; Medow, Joshua (International Journal of Infection Control, 2013)
This study evaluated the utility of the original and modified Clinical Pulmonary Infection Score (CPIS) compared with the National Healthcare Safety Network (NHSN) surveillance definition of VAP. The kappa statistic was 0.81 when comparing original CPIS and NHSN and 0.39 when comparing modified CPIS and NHSN. The CPIS score has good correlation with NHSN criteria and may have a role in VAP surveillance. Further research is essential to identify an optimal reference standard for VAP surveillance.